Critical Regionalism Approach for Djami Mosque Design Towards the Aesthetics of Sustainability - Mohd Hanif Masridin; Alice Sabrina Ismail (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2022)
Sustainable architecture seeks to minimize the negative environmental impact of buildings by efficiency and moderation in the use of materials, energy, development space and the ecosystem at large. It adopts a conscious approach to energy and ecological conservation in designing the built environment. This conscious process involves the embodiment of phenomenology as embedded in the critical regionalism approach that explains 'human experiences as being' in the built environment. In this sense, the aesthetics of sustainable architecture may be accomplished when three factors (the visual perception of space, spatial, experiential perceptions, and the cognition of the natural environment) are incorporated together. This paper aims to identify and unveil how the critical regionalism approach contributes to sustainable architectural design based upon five determinants - placemaking, genius loci, the phenomenology of senses, climatic and environment responsiveness, and communal and humanity tectonic. In Malaysia, the critical regionalism approach is not widely explored and defined due to a lack of value application and awareness amongst local designers in public building design. Hence, it resulted in public building design like Mosque that emphasizes only superficial aesthetics, which lacks importance on the user's needs. The study used the hermeneutic method through the interpretivism paradigm to understand this. As a case study, the two indicators of architectural elements, form making and spatial elements of mosque buildings, are analyzed to document the value of critical Regionalism that embraces adaptability, reinterpretation and realization of reality. This study will benefit many parties in providing recommendations for mosque design, referring to the critical regionalism approach toward sustainable architecture. This critical regionalism approach can foster the formation of a national identity architecture that can contribute to the unity of society and strengthen the sentiment of nationalism in the present Muslim and multi-racial society. In addition, by having a better-quality design, the built form can readily be accepted and adopted in terms of functions for the benefit of the entire community.